1989
DOI: 10.1159/000293523
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Aminobutyric Acid, Its Related Enzymes and Receptor-Binding Sites in the Human Ovary and Fallopian Tube

Abstract: The concentration of Γ-aminobutyric acid (GABA), the activities of related enzymes, i.e. glutamate decarboxylase and GABA transaminase, as well as the level of specific GABA binding sites were determined in ovaries and fallopian tubes obtained surgically from 31 women. None of the biochemical parameters examined showed a correlation with the age and hormonal background (serum estradiol and progesterone levels) of the patients. The respective ovarian and tubal values did not differ significantly in groups opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Inclusion of 80 lM ATA abrogated all these responses (Fig. 3A-D), further confirming the involvement of PLA 2 .…”
Section: Stimulation Of Acrosomal Exocytosis By Gabasupporting
confidence: 68%
See 4 more Smart Citations
“…Inclusion of 80 lM ATA abrogated all these responses (Fig. 3A-D), further confirming the involvement of PLA 2 .…”
Section: Stimulation Of Acrosomal Exocytosis By Gabasupporting
confidence: 68%
“…Staurosporine, at the low concentration used in this study, may be acting on PKC and the effect is similar to that seen with chelerythrine chloride (another, more specific PKC inhibitor) on PLA 2 and exocytosis stimulated by progesterone or ZP [22]. 2 is regulated by the MEK-ERK1/2 pathway In a previous study, we found that progesterone-and ZP-induced PLA 2 activation is regulated by PKA and PKC [22]. Here, we tested in two series of experiments whether PLA 2 activation and exocytosis induced by GABA, progesterone or ZP is regulated by the MEK-ERK1/2 pathway.…”
Section: Stimulation Of Acrosomal Exocytosis By Gabasupporting
confidence: 62%
See 3 more Smart Citations